the Effectiveness of Red Betel (Piper crocatum) Leaf Ethanol Extract Mouthwash in Reducing Dental Plaque Index - Siregar, Rawati; S, Sondang; Aritonang, Netty Jojor (Asian Journal of Pharmaceutical Research and Development, 2021)
Objectives: The purpose of this research was to determine the difference in the effectiveness of mouthwash of red betel leaf extract on the dental plaque index. Design:This research design is Quasi experimental. The ethanol extract of red betel leaf was prepared in various concentrations for use by the correspondents as a mouthwash. Dental plaque was observed before and after treatment, then compared the differences in results between groups. Interventions:The intervention variable in this study was a mouthwash preparation containing 4% and 5% ethanol extract of red betel leaf, then compared with a positive control mouthwash preparation containing Chlorhexidine. Main outcome measure:The results showed a decrease in the dental plaque index in the correspondents who were given mouthwash containing 4% and 5% red betel leaf ethanol extract. The anova test showed a significant difference between the dental plaque index between before and after treatment (p <0.05). Conclusion:Mouthwash containing ethanol extract of red betel leaves is effective in reducing the dental plaque index value.